Foramen tympanicum prevalence in the population of Southeast Brazil: a morphological study in computed tomography scans - Ribeiro, T. M.C.; Freire, A. R.; Daruge, E.; Botacin, P. R. [UNESP]; Prado, F. B.; Rossi, A. C. (VM Media Group sp. z o.o, 2022)
Background: The foramen tympanicum is located on the anteroinferior region of the external acoustic meatus and posteromedial to the temporomandibular joint in children between the 1st and the 5th year of life. It is considered an anatomical variation when it persists in adults. The aim of this study was to verify the prevalence as well as to characterise the foramen tympanicum in computed tomography (CT) scans of the population from southeastern part of Brazil. Materials and methods: A total of 78 CT scans of dry human skulls (20 female and 58 male) were used, which were selected randomly regarding the ages, ranged from 15 to 100 years. The foramen tympanicum was identified in the images of the axial plane and confirmed in the images of the coronal and sagittal planes. The largest diameter (in mm) was obtained. The descriptive statistics (in %), Fisher's test and χ2 test were performed to compare the prevalence of foramen tympanicum between sexes and sides. The probability value ≤ 0.05 was defined as a level of significance. Descriptive statistics were performed to verify the mean diameter of the foramen on the right and left sides of the skulls. Results: The prevalence of foramen tympanicum was higher in females (p = = 0.0070), bilaterally, as the absolute values of females were lower in relation to males. Fisher's exact test showed that the prevalence of foramen tympanicum was significantly higher in females (45%) than in males (15.52%). On the right side, the mean axial diameter was 2.23 mm (range 0.93.3.75 mm). On the left side, the mean axial diameter was 2.22 mm (range 0.9.3.61 mm). Conclusions: The knowledge of anatomical variations is extremely valuable for an accurate diagnosis, treatment plan and prognosis and a thorough preoperative assessment.
Keywords: anatomy; computed tomography; foramen tympanicum; Huschke's foramen; temporomandibular joint; tridimensional morphometry